Bilingual language experience and the neural underpinnings of working memory. (10th December 2021) - Kousaie, Shanna; Chen, Jen-Kai; Baum, Shari R.; Phillips, Natalie A.; Titone, Debra; Klein, Denise
Abstract: A longstanding question in cognitive neuroscience and in the bilingualism literature is how early language experience influences brain development and cognitive outcomes, and whether these effects are global or specific to language-related processes. The current investigation examined the effect of the timing of language learning on the performance and neural correlates of phonological and non-verbal working memory, subcomponents of executive function. Three groups of bilinguals, who varied in terms of the timing of second language learning (i.e., simultaneous bilinguals learned their two languages from birth; early and late bilinguals who learned their second language before or after 5 years of age, respectively), performed phonological and non-verbal working memory tasks in the magnetic resonance imaging scanner. Results showed that there were no group differences in performance on either of the tasks, or in the neural correlates of performance of the non-verbal task. However, critically, we showed that despite similar behavioural performance, the groups differed in the patterns of neural recruitment during performance of the phonological working memory task. The pattern of group differences was non-linear, demonstrating similar neural recruitment for simultaneous and late bilinguals that differed from early bilinguals. Findings from the current study suggest a dynamic mapping between the brain and cognition, contributing to our current understanding of the effect of the timing of language learning on cognitive processes and demonstrating a specific effect on language-related executive function. Highlights: Timing of L2 learning does not impact working memory (WM) performance. Timing of L2 learning selectively impacts neural recruitment for phonological WM. The impact of the timing of L2 learning on neural recruitment is non-linear.